Tickle the duck! - Long, Ethan (New York, NY : Little, Brown & Co., 2006)
Are you ticklish? This duck sure is!.
On board pages. Title from cover.
Keywords: Tickling -- Juvenile fiction; Ducks -- Juvenile fiction; Toy and movable books; Board books